PENGAMATAN MUTU HASIL BEBERAPA VARIETAS PADI (Oryza Sativa L) LOKAL ACEH - Ayu Linda Sari; Cut Mulyani; Yenni Marnita (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2023)
This study aims to determine the yield quality of several Acehnese local rice varieties (Oryza Sativa L). This research was carried out from October 2020 to March 2021. Rice cultivation was carried out in the rice fields of farmers in Gampong Paya Tenggar, Manyak Payed District, Aceh Tamiang Regency, and observations were made at the Agrotechnology Laboratory of Samudra University and the Laboratory of Chemical Analysis of Foodstuffs, Faculty of Agriculture, University of North Sumatra. This study used a non-factorial completely randomized design (CRD) using 5 Aceh local rice varieties, namely Inpari 32, UA-12 Sigupai, UA-11, US-02 Batuta and Gaptas. The parameters observed in this study included: milled rice yield, head rice yield, percentage of broken rice, percentage of rice groats, amylose content and gelatinizaion temperature. The results of the study of the best quality and variety were found in the UA-12 Sigupai variety and the Gaptas variety. These two varieties have met the requirements of the SNI standard, including the medium quality.